Living in darkness: Exploring adaptation of Proteus anguinus in 3 dimensions by X-ray imaging. (5th April 2022) - Tesařová, Markéta; Mancini, Lucia; Mauri, Edgardo; Aljančič, Gregor; Năpăruş-Aljančič, Magdalena; Kostanjšek, Rok; Bizjak Mali, Lilijana; Zikmund, Tomáš; Kaucká, Markéta; Papi, Federica; Goyens, Jana; Bouchnita, Anass; et al.
Abstract: Background: Lightless caves can harbour a wide range of living organisms. Cave animals have evolved a set of morphological, physiological, and behavioural adaptations known as troglomorphisms, enabling their survival in the perpetual darkness, narrow temperature and humidity ranges, and nutrient scarcity of the subterranean environment. In this study, we focused on adaptations of skull shape and sensory systems in the blind cave salamander, Proteus anguinus, also known as olm or simply proteus—the largest cave tetrapod and the only European amphibian living exclusively in subterranean environments. This extraordinary amphibian compensates for the loss of sight by enhanced non-visual sensory systems including mechanoreceptors, electroreceptors, and chemoreceptors. We compared developmental stages of P. anguinus with Ambystoma mexicanum, also known as axolotl, to make an exemplary comparison between cave- and surface-dwelling paedomorphic salamanders. Findings: We used contrast-enhanced X-ray computed microtomography for the 3D segmentation of the soft tissues in the head of P. anguinus and A. mexicanum . Sensory organs were visualized to elucidate how the animal is adapted to living in complete darkness. X-ray microCT datasets were provided along with 3D models for larval, juvenile, and adult specimens, showing the cartilage of the chondrocranium and the position, shape, and size of the brain, eyes, and olfactory epithelium. Conclusions: P. anguinus still keeps some of its secrets. Our high-resolution X-ray microCT scans together with 3D models of the anatomical structures in the head may help to elucidate the nature and origin of the mechanisms behind its adaptations to the subterranean environment, which led to a series of troglomorphisms.